2021
DOI: 10.1116/6.0000579
|View full text |Cite
|
Sign up to set email alerts
|

Effect of zinc content on the microstructure, in vitro bioactivity, and corrosion behavior of the microarc oxidized Mg–xZn–0.6Ca (x = 3.0, 4.5, 6.0) alloy

Abstract: Bioceramic calcium phosphorus (CaP) coatings were prepared on self-designed Mg–xZn–0.6Ca (x = 3.0, 4.5, 6.0 wt. %) alloy by microarc oxidation (MAO). The corrosion resistance, bioactivity, and biodegradability of the CaP coatings prepared on alloys with different zinc (Zn) contents were systematically studied and discussed by potentiodynamic polarization and in vitro immersion tests in the simulated body fluid solution. The CaP coatings and corrosion products were characterized by scanning electron microscopy,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…The baselines of all studies were balanced approximately, see Table 1. Among the 11 included studies, 3 studies [10,12,18] adopted the random number table method for grouping; 2 studies [16,17] took the lottery method; 5 studies [11,14,15,19,20] only mentioned randomness, and 1 study [13] did not mention grouping method. Allocation hiding was not mentioned in all studies.…”
Section: The Basic Characteristics and Quality Evaluation Included In...mentioning
confidence: 99%
See 2 more Smart Citations
“…The baselines of all studies were balanced approximately, see Table 1. Among the 11 included studies, 3 studies [10,12,18] adopted the random number table method for grouping; 2 studies [16,17] took the lottery method; 5 studies [11,14,15,19,20] only mentioned randomness, and 1 study [13] did not mention grouping method. Allocation hiding was not mentioned in all studies.…”
Section: The Basic Characteristics and Quality Evaluation Included In...mentioning
confidence: 99%
“…Allocation hiding was not mentioned in all studies. The blind method was involved in 2 studies, [10,12] while the rest studies [11,[13][14][15][16][17][18][19][20] did not mention it. The results of 1 study [16] were selectively reported, and none of the studies had bias from other sources.…”
Section: The Basic Characteristics and Quality Evaluation Included In...mentioning
confidence: 99%
See 1 more Smart Citation
“…Calcium is used in a variety of biomaterials and is a major ingredient in the body’s bones ( Ling et al, 2021 ). Moreover, degradation products of calcium-rich phosphate not only contribute to the integration of Zn implants with host bone, but also regulate the microenvironment of tissues around implants and promote new bone formation ( Wang et al, 2021 ). Theoretically, the surface modification of Zn-based alloys by phosphate chemical conversion technology has a broad application prospect.…”
Section: Introductionmentioning
confidence: 99%
“… YS (MPa) and elastic modulus (GPa) of Mg and its alloys are more similar to natural bone than those of other biodegradable metallic materials (such as Fe and Zn) and Polyetheretherketone (PEEK) ( Chen et al, 2022 ; Wang et al, 2022 ). …”
Section: Introductionmentioning
confidence: 99%